Elastic constants of nanoporous III-V semiconductors. (19th May 2015) - Janovská, Michaela; Sedlák, Petr; Kruisová, Alena; Seiner, Hanuš; Landa, Michal; Grym, Jan
Abstract: Resonant ultrasound spectroscopy is applied to determine elastic constants of nanoporous gallium arsenide and indium phosphide single crystals with various pore morphologies. Three samples with approximately the same level of porosity (30%) are studied; it is shown that in all cases this porosity leads to a decrease of Young's moduli by more than 50% and to a significant increase of the Poisson's ratios, while the strength of the resulting elastic anisotropy of the nanoporous material follows from the particular morphology of the pores. The experimentally obtained elastic constants are compared to those predicted for the given morphologies by finite elements modeling. It is observed that the numerical models give acceptably realistic predictions of the elastic constants, although they tend to underestimate the decrease of the elastic moduli due to the porosity as well as the corresponding increase of the Poisson's ratio.